Assistance Planning Production and Marketing Of Sticky Rice Tape in Micro, Small and Medium Enterprises (MSMes), Bakunglor Village, Jamblang Regency Towards Technology-Based Entrepreneurs - Ridwan Usman; Elfitria Wiratmani; Mei Lestari; Rayung Wulan; Sutrisno Sutrisno; Agus Riyanto; Ni Wayan Parwati S; Irwan Agus M (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This community service aims to provide solutions to problems faced by partners in providing input to small and medium enterprises (MSMEs) to be able to make good production plans so that they can measure raw material inventories, production processes to stock goods. The main objective is to maximize customer service, supply inventory, production planning, and control. Extensive marketing development provides advantages because the production results that have been carried out can be distributed well, so MSE needs to master various kinds of e-commerce in sales systems that involve information and communication technology. The stages of activity include preparation, implementation, evaluation of the results of this community service activity, namely production carried out by measurable and targeted partners so that it can provide economic value and clear expenditure and income planning related to the amount of production, the time needed in managing sticky rice tape production and understanding of participants e-commerce such as Tokopedia, Shopee, Instagram, Facebook are expected to be able to provide a maximum increase in marketing so that Bakunglor sticky rice tape can be enjoyed by glutinous tape lovers without having to wait a certain time to enjoy it.